PENGARUH HARGA DAN PERCEIVED QUALITY TERHADAP KEPUASAN KONSUMEN NETBOOK ACER PADA MAHASISWA UNIVERSITAS NEGERI PADANG - Renita Dewiva; Gesit Thabrani (Jurnal Praktik Bisnis, 2015)
This research aims to analyze: (1) influence of price toward customer satisfaction of Acer Netbook to student of Universitas Negeri Padang, (2) influence of perceived quality toward customer satisfaction of Acer Netbook to student of Universitas Negeri Padang. This research is causative, which is explain about influence of price and perceived quality toward customer satisfaction of Acer Netbook to student of Universitas Negeri Padang. Population in this research is all students of Universitas Negeri Padang who is using Netbook Acer. Samples has taken by using Accidental Sampling with total samples are 100 respondents. Primary data has taken through questionaire which is filled in by the respondents. Instrument test has done by validity test and realibility test. Technique analyze was using multiple regression analysis through SPSS 16.0. This research showed that (1) price has significant influence toward customer satisfaction of Acer Netbook to student of Universitas Negeri Padang (2) perceived quality has significant influence toward customer satisfaction of Acer Netbook to student of Universitas Negeri Padang. Key word: Price, Perceived Quality, and Customer Satisfaction.